Faktor-Faktor Mempengaruhi Pemahaman Operator SIMAK BMN Mengenai Penatausahaan Barang Milik Negara - Lolli Adriani; Suhairi Suhairi (Jurnal Ecogen, 2022)
The level of education of an employee shows the level of knowledge and understanding in carrying out the tasks at hand. Through education a person’s quality can be improved in various aspects because educated people will be more rational in thinking and acting, understanding duties and responsibilities. So, the perception of the benefits of education felt by SIMAK BMN operators during their education level helps in completing their duties and responsibilities and makes operators more effective in operating SIMAK BMN.Although it has been supported by legislation that is used as a reference and legal force in the management of state property, there are still many problems and difficulties that hinder the management of state property in the implementation in the field. One of the problems is in the administration of state property. There are still many SIMAK BMN operators in the Regional Office of the Ministry of Law and Human Rights of West Sumatra who do not understand the rules for administering state property, especially the Regulation of the Minister of Finance Number 181/PMK 06/Year 2016. As a technical implementer in the administration of State Property, it is important for the SIMAK BMN operator to understand these rules so that the administration of state property is carried out properly and the reports of state property produced are reliable and accountable.Keywords : Operator, Administration